Myanmar Agricultural Performance Survey (dry season 2023): Farm commercialization - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Key Findings This Research Note presents the results from an assessment of farm commercialization in Myanmar after the dry season of 2023, based on data from a phone survey – the Myanmar Agriculture Performance Survey (MAPS) – that was conducted with 5,001 crop farmers in all states/regions of the country, over the period June – July 2023. It is found that:  The security situation is worrisome for farmers. Almost a quarter of the farmers reported feeling ‘very insecure’ or ‘insecure’ during the period of the interview.  Agricultural inputs were mostly available during the 2023 dry season period. However, it was difficult to access labor for 17 percent of the farmers. Conflict-affected areas suffered substantially more from labor availability problems.  Input prices during the dry season of 2023 increased compared to the same period in 2022 by 14 percent for urea, 19 percent for mechanization, and 15 and 22 percent for hired labor of men and women, respectively.  Farmgate prices are all on the rise compared to a year earlier. Paddy prices increased by 69 percent. Other farm prices showed mostly lower price increases. In the case of pulses, black gram increased by 21 percent and green gram by 19 percent. In the case of oilseeds, sesame increased by 38 percent and groundnut by 33 percent.  The high price increases in the case of paddy and oilseeds – higher than input costs – reflects increased profitability for these farmers. However, that is not the case of these other crops.  Most farmers reported higher crop sales income this year compared to last. Farms affected by cyclone Mocha and farms in insecure areas however reported relatively more crop sales income decreases than other farmers. Recommended Actions  The increasing insecurity in the country is hampering the functioning of agricultural markets (leading to lower availability of agricultural inputs and lower incomes). An improved security situation is called for.  As cyclone Mocha has reduced, among others, incomes of a large number of farmers in Rakhine and the Dry Zone, assistance of these cyclone-affected farmers is needed.